A Psychocultural Model of Transcultural Communication - Shafiullah, Mohammed (Advances in Social Sciences Research Journal, 2023)
Analysis of the dynamic interplay of philosophical, social and psychological processes informs us about the underlying mechanisms of transcultural communication. The current paper proposes a novel psycho-cultural model based on an understanding of the interplay of cultural and psychological processes in communication between cultures. Analysis of the dynamic interplay of philosophical, social and psychological processes informs us about the underlying mechanisms of transcultural communication.